SYNTHESIS AND CHARATERISATION OF RICE HUSK SILICA BASED BOROSILICATE (B2SiO5) CERAMIC BY SOL-GEL ROUTES - Simon Sembiring (Universitas Gadjah Mada, 2011)
In this research, borosilicate ceramics were produced from rice husk silica. Preparation of borosilicate ceramics was conducted by mixing boron oxide sol from borax with silica sol extracted from rice husk. The boron oxide was produced by hydrolysis of borax using H2SO4 5%. The samples were synthesized with different compositions, with the ratios of silica to boron oxide are 8:1, 8:2, 8:3 and 8:4. The samples were sintered at 900 °C. Functional groups were examined using FTIR spectroscopic technique. Structural and microstructural characteristics were examined by XRD and SEM, respectively. The chemical resistance of borosilicate is evaluated by gravimetric method using H2SO4, HCl, NaOH and KOH. The FTIR study revealed that the main functional groups are Si-O-Si, B-O-B, and B-O-Si. The x-ray diffraction (XRD) study revealed that the main crystalline phases are borosilicate (B2SiO5) and boron oxide (B2O3). SEM investigations clearly demonstrated that the smaller particle size was found with increasing in boron oxide concentration. From the chemical resistance test carried out, it was obtained that the produced borosilicate possessed high resistance to acids and alkalis.